Age-Dependent Decline in Salinity Tolerance in a Euryhaline Fish - Inokuchi, Mayu; Yamaguchi, Yoko; Moorman, Benjamin P.; Seale, Andre P. (Frontiers in Aging, 2021)
Euryhaline teleost fish are characterized by their ability to tolerate a wide range of environmental salinities by modifying the function of osmoregulatory cells and tissues. In this study, we experimentally addressed the age-related decline in the sensitivity of osmoregulatory transcripts associated with a transfer from fresh water (FW) to seawater (SW) in the euryhaline teleost, Mozambique tilapia, Oreochromis mossambicus. The survival rates of tilapia transferred from FW to SW were inversely related with age, indicating that older fish require a longer acclimation period during a salinity challenge. The relative expression of Na+/K+/ 2Cl- cotransporter 1a (nkcc1a), which plays an important role in hyposmoregulation, was significantly upregulated in younger fish after SW transfer, indicating a clear effect of age in the sensitivity of branchial ionocytes. Prolactin (Prl), a hyperosmoregulatory hormone in O. mossambicus, is released in direct response to a fall in extracellular osmolality. Prl cells of 4-month-old tilapia were sensitive to hyposmotic stimuli, while those of >24-month-old fish did not respond. Moreover, the responsiveness of branchial ionocytes to Prl was more robust in younger fish. Taken together, multiple aspects of osmotic homeostasis, from osmoreception to hormonal and environmental control of osmoregulation, declined in older fish. This decline appears to undermine the ability of older fish to survive transfer to hyperosmotic environments.